Testing the Impact of Electronic Information System on Employees’ Performance in Jordanian Industrial Companies - Md Faruk, Abdullah; Bunyamin Adewale, Bello; Emad, Abed Ganahreh (2018)
Despite the significant contributions of electronic information system that were highlighted by literature, yet studies investigating the impact of electronic information system on employees’ performance in Jordan industrial context are quite limited. Hence, this study is conducted to examine the Impact of Electronic Information System on Employees’ Performance in Jordanian Industrial Companies. The data was collected from 63 industrial companies in Amman Stock Exchange, whereas simple random sampling was used to select 433 administrative employees who served as respondents in the survey. Exploratory factor analysis EFA and CFA were conducted on the constructs before proceeding to run the Structural Equation Modeling in AMOS 24. The results of the study of Structural Equation Model reveled that electronic information system has a statistically significant positive direct effect on employees’ performance. Conclusively, it could be deduced that the application of electronic information system in Jordanian industrial companies was quite high. This is logical because of increased competition in the industrial sector, both internally and externally, as well as the widespread availability and low cost of the electronic information system in Jordan, compared to other countries and the government initiatives, which encourage the use of technology in different sectors.